Implementation of Cooperative Learning Strategies in Islamic Religious Education - Badrus Zaman (IJECA (International Journal of Education and Curriculum Application), 2020)
PAI teachers in implementing cooperative learning strategies namely by conveying information verbally and students working together in groups to process information. When studying groups, PAI teachers evaluate students to see the group's success. The steps in cooperative learning can be achieved if there is an effort to increase student participation, facilitate students with experience leadership attitudes and always provide opportunities for students to learn and interact with students with different backgrounds. Implementing cooperative learning strategies requires good cooperation between team members. Students are the focal point of the learning process. The teacher as a facilitator as well as a moderator for the sustainability of cooperative learning strategies. The purpose of implementing a cooperative learning strategy has three important objectives, namely the first objective cooperative learning is intended to increase the activity of students in important academic tasks (academic achievement). The second goal is tolerance and broader acceptance of people of different races, cultures, social classes, or abilities (tolerance and acceptance of diversity). The third goal is to teach the skills of collaboration and collaboration with students (Social Skills Development).